Public Policy in Digital Society - Vasilenko, L.A. (KnE Social Sciences, 2021)
The objectives of the article are to consider new possibilities of controllability in the context of digitalization and the becoming of a society with new characteristics and development trends. In the twentieth century, under the influence of digitalization, new trends and development threats appeared in the world associated with a sharp increase in the complexity of social processes, the intensive development of information technologies and the network structure society formation, which caused many new forms of communication. Society gradually attempts to become an ‘adult’ in this upcoming digital world — we can see it by the quality characteristics of Generation Z. But it loses something very important. The society has already realized that it is necessary to revise the semantic accents of the “public administration” term, shifting them towards the term “controllability”. But how to do it whether it is necessary to do it? The author’s thoughts and conclusions are based on sociological studies over the past 7–8 years, including: a comprehensive study “Dialogue of power and society in Internet communications (2013–2015); Global Digital Overview. 2020 and All Internet statistics for 2020 — figures and trends in the world and in Russia; ”Analysis of Russian media and Russian-language social media”, using the Medialogy information system (2015–2020). Keywords: Public Administration, Digital Society, digitalization, controllability, social network